2023
DOI: 10.3390/en16010555
|View full text |Cite
|
Sign up to set email alerts
|

Energy Efficient Received Signal Strength-Based Target Localization and Tracking Using Support Vector Regression

Abstract: The unpredictable noise in received signal strength indicator (RSSI) measurements in indoor environments practically causes very high estimation errors in target localization. Dealing with high noise in RSSI measurements and ensuring high target-localization accuracy with RSSI-based localization systems is a very popular research trend nowadays. This paper proposed two range-free target-localization schemes in wireless sensor networks (WSN) for an indoor setup: first with a plain support vector regression (SVR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Pre-processing: The data collected from the healthcare institution contained a lot of noise. Thus, the raw data were preprocessed to remove noise and other unwanted features before the final analysis can begin [25,26].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pre-processing: The data collected from the healthcare institution contained a lot of noise. Thus, the raw data were preprocessed to remove noise and other unwanted features before the final analysis can begin [25,26].…”
Section: Methodsmentioning
confidence: 99%
“…Key considerations in configuring an SVM model include the choice of kernel function, such as the linear kernel for linearly separable data or the RBF kernel, a versatile option used for capturing intricate relationships within complex datasets, like those shown in [24,25].…”
Section: Building Machine Learning Modelsmentioning
confidence: 99%
“…It is found that the proposed OSS-SVR scheme is robust enough for variations in system noise and need very smaller amount of labeled data during training. The SVR-based target localization model can also be fused with KF to smoothen the target location estimates [27]. The proposed SVR model utilizes linear, Sigmoid, RBF, and polynomial kernel functions to estimate the moving target locations in indoor.…”
Section: Related Workmentioning
confidence: 99%
“…The most classic localization algorithms for WSNs include ToA [22], TDoA [23], AoA [24] and RSSI [25]. However, these algorithms cannot guarantee the accuracy and energy of localization when they are used in sparse and harsh underwater environments.…”
Section: Related Workmentioning
confidence: 99%